Analisis Pembelajaran Nasikh Mansukh dan Muhkam Mutasyabihat dalam Al-Qurán - Ratna Komalasari (PT. Nawa Edukasi Nusantara, 2025)
Nasikh is copying one verse from one to another. As for Mansukh, it is a postulate or verse that is copied. Nasikh and mansuk are also related to muhkam mutasyabihat where the verses of muhkam mutasyabihat are verses that contain halal and haram, so that the mahkam verse is a verse that is not covered by mansukh while the mutasyabih verse is a verse that is dinasakh. The purpose of the discussion of Nasikh Mansukh and mahkam mutasyabihat in the Qur'an is of course to determine the verses that can be replaced or moved from one place to another, in addition to knowing the halal haram position of the intended verse. In this article, not all verses of the Qur'an can be understood easily and some are even difficult. It is considered easy because it can be understood with just one look, but it is considered difficult because it takes a long time to understand. Verses that are easy to understand are called nasikh while verses that are difficult or not easy to understand are called mahkam mutasyabihat.